IMPLEMENTASI METODE HOUSE OF RISK PADA PENGELOLAAN RISIKO RANTAI PASOKAN HIJAU PRODUK BOGIE S2HD9C (Studi Kasus: PT Barata Indonesia) - Maghfur Rozudin; Nina Aini Mahbubah (Fakultas teknik Universitas Muhammadiyah Jakarta, 2021)
In carrying out its business processes, PT Barata Indonesia requires raw material supply and services from related partners to be able to complete work on time. But increasingly complex business competition makes the company inseparable from a risk that can disrupt the normal operation of the system. Therefore supply chain risk management is needed in managing supply chain activities to reduce the impact of the risk. This study uses the House of Risk (HOR) method with the GSCOR approach to minimize the occurrence of risks and potential risk events that can occur in the company's business processes. The results of the identification with the tools why why analysis and the calculation of the house of risk method, identified 82 risk events, 22 risk agents and 22 risk minimization actions. Of the 22 risk agents, 10 risk agents are prioritized based on the largest ARP value in the calculation of HOR1 and 10 risk minimization actions on HOR2 based on the greatest value of Effectiveness to Difficulty Ratio. Based on the results of the analysis of 10 priority risk minimization actions from the calculation of HOR2 obtained 5 risk mitigation strategies namely, 1) implementing the HR development strategy, 2) conducting information disclosure and a customer-focused approach, 3) Determining supplier selection policies that are green certified, 4) procurement planning inverter, 5) Good communication with third parties and partnersek).